Entre « développement » et conservation des aires naturelles : jeux de pouvoir, conflits d’usage et marginalisation dans la vallée du Kilombero en Tanzanie - Adriana Blache (Belgeo)
In this article, we discuss the colonial continuities of space production in the Kilombero Valley in Tanzania and its territorialisation, from the design and implementation of protected areas to the complementarities between the “preservation/conservation” of an idealized “Nature” and the establishment of productive territory. Through the concept of “corridor and the clusters” for a green agricultural modernization that it draws, SAGCOT’s strategic and planning model is the new avatar of a “greening” liberal development model since the colonial era. The research question focuses on the production of space and its contradictions in the historical time of colonial and postcolonial development, by questioning the continuities or discontinuities introduced by contemporary dynamics. In a first part, we will see that “Nature”, placed at the center of colonial and postcolonial reserves already allowed their exploitation for arboriculture or tourism. In a second part, we will see that beyond the conservationist discourse, this “Nature” can serve as a source of resources for extractive activity within the reserves themselves and for agricultural development in the interstices of environmental conservation.